Analysis of Porcine Gelatin in Hard Capsule Shells by Using A Combination of FTIR and Principal Component Analysis Methods - Zilhadia; Mabrurotul Mustafidah; Herdini; Chairul Amin Muhammad (JSFK (Jurnal Sains Farmasi & Klinis), 2026)
This study aims to conduct a halal analysis of hard capsule shells by using a combination of Fourier Transform Infrared (FTIR) and Principal Component Analysis (PCA) methods. The study was conducted by extracting gelatin from commercial hard capsule shells containing drugs and then measuring their absorbance by using FTIR. As a comparison, gelatin extracted from a simulated hard capsule shell was used. The FTIR spectrum data was analyzed by using PCA. The results of the analysis showed that the FTIR spectra of bovine and porcine gelatin were very similar, but PCA could classify the differences. The absorbance (appearing as a spectrum peak), which plays a significant role in the classification of bovine and porcine gelatin, was at wavenumbers 1455 cm-1 and 1409 cm-1. The PCA analysis showed that samples A and D had properties similar to porcine gelatin, sample C had properties similar to hard capsule shells made from porcine gelatin, sample B had properties similar to bovine gelatin, and sample E had properties similar to hard capsule shells from bovine gelatin. These results indicate that bovine gelatin and porcine gelatin in simulated hard capsule shells can be distinguished based on the FTIR spectrum combined with PCA. Commercial hard capsule shells can be classified based on their similar properties to bovine and porcine gelatin. However, this research could not confirm the exact source of the gelatin.